How to Broaden the Tax Base of the Excise and Taxation Department in Punjab - Malik, Sobia (Journal of Public Policy Practitioners, 2025)
Broadening the tax base is crucial for ensuring fiscal sustainability in Punjab, where the Excise and Taxation Department manages key levies, including Property Tax, Motor Vehicles Tax, and Professional Tax, which collectively generate over 45% of the department’s total revenue. Despite digitization efforts—such as the computerization of the motor taxation system since 2007 and the property tax system since 2014—Punjab still collects only 40–50% of the potential property tax revenue due to outdated rental values, widespread exemptions, and unassessed units despite technological interventions like self-assessment of property units and imposition of DC rates. For instance, over 1.9 million, which is 30% of total urban property units, remain either under-assessed or exempt, eroding the revenue base by an estimated PKR 50 billion annually. Drawing on governance theory, the study combines recent tax collection trends, focused group discussions, semi-structured interviews with more than 30 key officials belonging to South Punjab, North Punjab and Central Punjab, document analysis. Comparative insights from India and Bangladesh show that digitization and public awareness campaigns can raise compliance by 15–20%, potentially adding billions to Punjab’s revenue. It also highlights how the lack of updated GIS mapping since 2013 has limited tax base expansion by failing to incorporate 15-20% of new properties each year. To address these gaps, the paper recommends strict enforcement of DC rate-based property valuations introduced in 2025, linking GIS with Urban immovable property tax (UIPT) systems to detect untaxed units in real time. Adopting advanced digital platforms for 100% e-payments, especially in remote districts and interdepartmental integration (PRA, PLRA, BoR and Finance), rationalization of exemptions, digital detection of unassessed/underassessed units in circles, zones, districts, division and all over Punjab. The findings emphasize that a broadened tax base could boost Punjab’s own-source revenue significantly, ensuring sustainable growth and better service delivery.